Gender Incongruence: clinical, psychological and therapeutic aspects - M. I. Yagubov; E. A. Starostina; N. V. Dobaeva; M. A. Ichmelyan (Медицинский вестник Юга России, 2022)
Recently, the issues of violations of gender identity are becoming more relevant and discussed, the number of patients with a request for a sex change is increasing. The complexity of this issue requires clinicians to be competent in helping transgender people, as they sometimes face many obstacles in the way of receiving care in medical institutions: the lack of specialists in the regions, a clear algorithm for helping transgender people, discrimination, stigmatization, and financial difficulties. At the same time, there are more and more foreign studies devoted to "detransition", i.e. "reverse" gender reassignment, which may indicate existing problems in the diagnosis of these conditions and methods of providing medical care to patients with gender identity disorders. The most difficult issues when working with patients experiencing gender dysphoria, in addition to identifying the true causes of gender identity disorders, are the preservation of fertility after gender-affirmative interventions, possible regrets after operations, and the provision of medical care to minors. Changes in the classification of gender disorders, including the exclusion of transsexualism from the class of mental disorders, creates the basis for discussions about the clinical, psychopathological and phenomenological features of these conditions. The scientific review provides information on the clinical and psychological aspects of gender identity disorders, as well as on therapeutic interventions for individuals with this pathology, using a multidisciplinary approach. Certain stages of the provision of medical and social assistance are described to reduce risks and more successful, professional assistance to persons with a gender incongruence.